2021
DOI: 10.1111/jfpp.15615
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis characteristics and aroma development during ripening of functional IranianLighvancheese

Abstract: Cheese is an excellent source of nutrition (particularly protein, calcium, phosphorus, and vitamins including A and D) and possesses high bioavailability and palatability (Uliescu et al., 2007). Grade milk and dairy products are an important and readily accessible source of animal-origin protein in the human diet. Lighvan, a traditional, semihard cheese, is produced mainly in northwestern Iran from raw sheep's milk or mixtures of sheep's and goat's milk, without a starter culture. The breeds of sheep and goats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These results suggest differences in the composition and characteristics of different whey cheese samples, which could be due to factors such as milk source, processing techniques, or ripening conditions. However, the RI value could be much higher in other aged cheeses (>10 %) (Miloradovic et al, 2018;Shahab Lavasani, 2021). The relatively low RI value in the whey cheese samples is probably due to the fact that no microorganisms or enzymes are used in the production process and the enzymatic activity of the natural microbiota is reduced due to the heating process during production.…”
Section: Acidity Water Holding Capacity and Ripening Index Values Of ...mentioning
confidence: 96%
“…These results suggest differences in the composition and characteristics of different whey cheese samples, which could be due to factors such as milk source, processing techniques, or ripening conditions. However, the RI value could be much higher in other aged cheeses (>10 %) (Miloradovic et al, 2018;Shahab Lavasani, 2021). The relatively low RI value in the whey cheese samples is probably due to the fact that no microorganisms or enzymes are used in the production process and the enzymatic activity of the natural microbiota is reduced due to the heating process during production.…”
Section: Acidity Water Holding Capacity and Ripening Index Values Of ...mentioning
confidence: 96%
“…Treonine decomposition also produces acetaldehyde and aldehydes with side branches such as 2-methylbutanol and 3methylbutanal are the result of leucine and isoleucine metabolism. With regard to aromatic aldehydes, these compounds are mainly formed starting from α-keto acids derived from the benzaldehyde released by the spontaneous oxidation of tryptophan and phenylalanine [7]. In general, the low amount of aldehyde compounds is attributed to the presence of reductases from cheese microbiota.…”
Section: Changes In Acetaldehyde (μG/g) Te Evaluation Of Ac-mentioning
confidence: 99%
“…Acetic acid forms during the early stages of ripening and is probably a product of citrate or lactate fermentation or of amino acid catabolism by bacteria [8]. Shahab Lavasani reported that the kind and quality of milk and the conditions of manufacturing and ripening are the most important factors afecting the concentration of acetic acid in Lighvan cheese [7].…”
Section: Changes In Acetic Acid (μG/gmentioning
confidence: 99%
See 1 more Smart Citation